Impact Of Covid-19 On Indian Stock Market - Dhillion, Mr. Anurag; Tyagi, Dr Vikas (The journal of contemporary issues in business and government, 2021)
Securities exchange is one of the most adaptable parts in the budgetary framework of a country, and Stock Market assumes a significant job in economic advancement. Securities exchange is a center point where facilities are given to the speculators to buy and sell their Shares, Bonds and Debenture and so forth. In Stock Market different organizations are inclined to their undertaking through public issuesBombay Stock Exchange (BSE), the National Stock Exchange (NSE) and the Calcutta Stock Exchange (CSE) are the recorded stock market in India. These three are biggest Indian Stock Market. But now Indian economy is facing a problem i.e. Corona virus. Corona virus or COVID19 are an enormous group of infections that can cause sicknesses running generally in seriousness. Its 1st case was recorded in Wuhan city, China. After that the disease spreads around the world and on 21st January 2020, India records its first case of COVID19. This virus has drastically affected the world's economy. Before corona virus phase, average NSE index nifty 50 was near to 12000 points and BSE SENSEX was around 41000 points. But from 21st January to 31st march, NIFTY 50 and SENSEX were massively down by 31.954% and 31.1769% respectively.